Activation of pro-survival metabolic networks by 1,25(OH)2D3 does not hamper the sensitivity of breast cancer cells to chemotherapeutics - Abu El Maaty, Mohamed A.; Dabiri, Yasamin; Almouhanna, Fadi; Blagojević, Biljana; Theobald, Jannick; Büttner, Michael; Wölfl, Stefan (Cancer & metabolism, 2018)
We have previously identified 1,25-dihydroxyvitamin D3 [1,25(OH)2D3], the bioactive form of vitamin D3, as a potent regulator of energy-utilization and nutrient-sensing pathways in prostate cancer cells. In the current study, we investigated the effects of 1,25(OH)2D3 on breast cancer (BCa) cell metabolism using cell lines representing distinct molecular subtypes, luminal (MCF-7 and T-47D), and triple-negative BCa (MDA-MB-231, MDA-MB-468, and HCC-1143).